Pre-Planning of Casing Seat Position to Choose Optimum Equivalent Circulation Density to prevent lost circulation - A.Razzaq, Ayad Abdulhaleem; A. Kzar, Wasan (Iraqi Journal of Science, 2022)
Loss of drilling fluid in the Nasiriyah oil field can be considered as a big,serious, and expensive problem at the same time, therefore accurate and integratedprogram must be prepared before start drilling in layers that are likely to get losscirculation. From the available data of well Ns-13, the area of loss was detected infive layers, which are Dammam, Um- radoma, Tayarat, Shiranish and Hartha sincethese layers contain natural cracks and high porosity represented by vugs.Methods of prevention have been identified by specifying the minimum valuesof drilling parameters to reduce hydrostatic pressure, thus reducing equivalentdensity of drilling mud during the circulation, depths of casing shoes isdetermined (2500 ft, 3550ft, 5300ft and 6894.5ft) to strengthen the wall of the welland prevent losses.